Risk factors for virological failure and subtherapeutic antiretroviral drug concentrations in HIV-positive adults treated in rural north western Uganda - Ahoua, Laurence; Guenther, Gunar; Anguzu, Paul; Suna, Balkan; Olson, David; Olaro, Charles; Pujades-Rodríguez, Mar (BMC infectious diseases, 2009)
Little is known about immunovirological treatment outcomes and adherence in HIV/AIDS patients on antiretroviral therapy (ART) treated using a simplified management approach in rural areas of developing countries, or about the main factors influencing those outcomes in clinical practice. Cross-sectional immunovirological, pharmacological, and adherence outcomes were evaluated in all patients alive and on fixed-dose ART combinations for 24 months, and in a random sample of those treated for 12 months. Risk factors for virological failure (>1,000 copies/ml) and subtherapeutic antiretroviral (ARV) concentrations were investigated with multiple logistic regression. At 12 and 24 months of ART, 72% (n = 701) and 70% (n = 369) of patients, respectively, were alive and in care. About 8% and 38% of patients, respectively, were diagnosed with immunological failure; and 75% and 72% of patients, respectively, had undetectable HIV RNA (<400 copies/ml). Risk factors for virological failure (>1,000 copies/ml) were poor adherence, tuberculosis diagnosed after ART initiation, subtherapeutic NNRTI concentrations, general clinical symptoms, and lower weight than at baseline. About 14% of patients had low ARV plasma concentrations. Digestive symptoms and poor adherence to ART were risk factors for low ARV plasma concentrations. Efforts to improve both access to care and patient management to achieve better immunological and virological outcomes on ART are necessary to maximize the duration of first-line therapy.
Keywords: Viral Load; Immune Reconstitution Inflammatory Syndrome; Undetectable Viral Load